THE ANALYSIS OF DIFFERENCES IN VISUAL PERCEPTION OF AXIAL VELOCITIES OBJECTS AND THEY IMAGES - E. G. Zaytseva; V. V. Nikitin (Приборы и методы измерений)
Differences in visual perception of objects and their two-dimensional images are analyzed in this research paper. Mathematical functions are given – they allow quantitatively estimate difference between axial velocities image of object as function for spectator and observer. This difference is equal to zero by parameters, that are found.